2014
DOI: 10.1177/0898264314549661
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Assessment and Factors Associated to Malnutrition in Older Adults

Abstract: The MNA is useful to evaluate factors associated with malnutrition among older adults in Bogotá. Malnutrition is associated with perception of poor health, comorbidities, number of medications, and cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
1
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 43 publications
4
19
1
7
Order By: Relevance
“…31 Many studies have used activities of daily living (ADL) and instrumental activities of daily living (IADL) scales for the assessment of functional status among elderly people. 13,17,28 In this study, the rates of ADL-dependency and IADL-dependency were significantly higher in malnourished group.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…31 Many studies have used activities of daily living (ADL) and instrumental activities of daily living (IADL) scales for the assessment of functional status among elderly people. 13,17,28 In this study, the rates of ADL-dependency and IADL-dependency were significantly higher in malnourished group.…”
Section: Discussionmentioning
confidence: 49%
“…7 In this study, higher income was inversely associated with malnutrition which was already reported in a study conducted among elderly people in Colombia where no income was significantly associated with a lower MNA score. 28 Other authors also revealed the same finding that elderly people who live in poverty are at greater risk of malnutrition. 19 This effect could be due to reduced food availability, consumption of food low in essential nutrients and growing food insecurity as a result of low income.…”
Section: Discussionmentioning
confidence: 74%
“…En Colombia, en un estudio realizado en las ciudades de Bogotá y Medellín, las dos principales capitales del país, la frecuencia de riesgo de desnutrición también fue más baja (34,3% y 41% respectivamente) comparada con la encontrada en el presente estudio 17,25 . El hecho de que el riesgo de desnutrición o la presencia de desnutrición en Tabla 1.…”
Section: Antecedentes Médicosunclassified
“…Enfermedades concomitantes 10,11 , síntomas depresivos 12 , alteración del estado cognitivo 13 y dependencia funcional 14 pueden incrementar el riesgo de desnutrición en esta población. Pocos estudios se han realizado en el contexto latinoamericano 15,16 y colombiano 17 , donde la población adulta mayor presenta condiciones de vulnerabilidad y descuido por parte del estado 18 , que hace necesario conocer la frecuencia de desnutrición o riesgo de desnutrición y los factores asociados, con el propósito de revisar las políticas públicas actuales.…”
unclassified
“…La versión que se utilizó consta de 21 ítems, cada uno de ellos compuesto por varias afirmaciones sobre un mismo síntoma depresivo, que se presentan ordenados de menor a mayor gravedad y entre los cuales la persona evaluada debió escoger el que mejor describiera su estado; cada afirmación de los diferentes ítems evaluados se puntúa de 0 a 3. La interpretación de los resultados del test es la siguiente: altibajos considerados normales (1-10), leve perturbación del estado de ánimo (11)(12)(13)(14)(15)(16), estados de depresión intermitentes (17)(18)(19)(20), depresión moderada (21-30), depresión grave (31-40) y depresión extrema (> 40) (23).…”
Section: Materiales Y Métodosunclassified